2010
DOI: 10.1051/forest/2010048
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity in Pinus pinaster δ13C: environment modulates genetic variation

Abstract: Keywords:carbon isotope / phenotypic plasticity / genetic variation / environmental interaction / water use efficiency Abstract • Carbon isotope composition (δ 13 C) is a complex trait involved in acclimation, adaptive processes and related to water use efficiency (WUE) and/or productivity.• To estimate the genetic variation in δ 13 C and growth (h), their relationship, and the genotype by environment interaction effect in both variables, we analyzed three Pinus pinaster populations and six to ten families per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 40 publications
4
48
0
1
Order By: Relevance
“…Previous work on maritime pine demonstrated that environmental variation influences population divergence in the plasticity of drought adaptive traits and the importance of genetic components in drought tolerance (Corcuera et al 2011). Despite the existence of P. pinaster genetic differentiation in response to drought stress (Corcuera et al 2010), there is only one study on the role of proline and phytohormones, particularly jasmonates, in the plastic responses to the environmental conditions of P. pinaster populations (Pedranzani et al 2007). In fact, there are few studies on the role of proline, ABA and JA as stress signals in forest trees, and the reports are even scarcer when seeking intraspecific differences.…”
Section: Introductionmentioning
confidence: 98%
“…Previous work on maritime pine demonstrated that environmental variation influences population divergence in the plasticity of drought adaptive traits and the importance of genetic components in drought tolerance (Corcuera et al 2011). Despite the existence of P. pinaster genetic differentiation in response to drought stress (Corcuera et al 2010), there is only one study on the role of proline and phytohormones, particularly jasmonates, in the plastic responses to the environmental conditions of P. pinaster populations (Pedranzani et al 2007). In fact, there are few studies on the role of proline, ABA and JA as stress signals in forest trees, and the reports are even scarcer when seeking intraspecific differences.…”
Section: Introductionmentioning
confidence: 98%
“…It spreads from Morocco to the French Landes and grows in a large variety of soil types and precipitation amounts, coping with diverse water availabilities. The species has shown a high level of population and/or family differentiation and plasticity throughout its natural geographical distribution in morphological and physiological parameters related to drought responses like carbon isotopic composition (Aranda et al 2010;Corcuera et al 2010;Correia et al 2008;Nguyen-Queyrens et al 1998;Tognetti et al 2000), gas exchange (Fernandez et al 2006), osmotic adjustment (Nguyen and Lamant 1989) and water relations (Fernandez et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…is a highly valuable Mediterranean coniferous species that grows under contrasting water availabilities (high in the Atlantic coasts of Portugal, Spain and France and much lower in continental Spain and the Mediterranean coasts of Southern Europe and North of Africa) [20]. Throughout its natural geographic distribution, this species exhibits a high level of population differentiation for survival [21], growth [22–26] phenology, and drought tolerance [14,27–29].…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of variation differs between drought related traits (e.g. water use and hydraulic efficiency and biomass allocation), presenting either uniform or divergent selection [20,33]. …”
Section: Introductionmentioning
confidence: 99%